A trail to milieu research methodology for application of implementation frameworks in manufacturing sector - Rafique, Muhammad Zeeshan; Mohd Nizam Ab Rahman; Nizaroyani Saibani; Norhana Arsad (Penerbit Universiti Kebangsaan Malaysia, 2020)
The profusely used tools of operational management research in lean manufacturing context include roadmap, conceptual model, implementation frameworks, descriptive planning and assessment checklist. Out of these, an implementation framework development in lean manufacturing sector is common, but faces quandary regarding its development, consolidation and validation – thereby confirming the requirement of availability of succinct platform that aids in research methodology development. The aim of this research is to attain a clear research context, achieved accordingly by detailed literature review study that would subsequently aid in developing a generic research methodology design framework. Concomitant to it, the four layers, the layers of research onion were discussed; followed by selection of appropriate methods for development of research methodology in order to arrive at implementation frameworks. It was observed that for the methodology development, the philosophy of pragmatism is highly suitable, followed by abductive logic, in case of technique, mixed mode research is best, whereas in strategy selection, case study strategy is the most suitable due to its multi-functional ability of in-depth operational study. In addition to that, the mixed-mode approach carries the ability of comparative qualitative and quantitative research through longitudinal and cross-sectional case study respectively. Furthermore, the data collection processes were discussed in relevance to the research objective, which culminated in the formation of a detailed research methodology which has been divided into three major stages of research context and approach, framework development and validation, resulting in attaining implementation framework through literature review, longitudinal case study and cross-sectional case study respectively. The major strength and contribution of this research study is the development of one concise research methodology that is considered as the paradigm shift and a clear innovation towards this field.